HOW COVID-19 HAD CHANGED BUSINESS ENVIRONMENT: DOES ENTREPRENEURIAL ATTITUDE & CRISIS MANAGEMENT PREVENTABILITY MODERATE THE RELATIONSHIP BETWEEN THE EFFECTS OF COVID-19 LOCKDOWN AND BUSINESS ENVIRONMENT. - Azam, Nauman; Kousar, Shakeela; Rasool, Zeeshan; Ali, Hina; Ahmad, Zaid (The journal of contemporary issues in business and government, 2022)
The purpose of this study is to investigate to what extentthe business environment is affected by the Covid-19 lockdownand to find out how businesses can go forwardby adopting the changes rapidly by using different concepts and strategies like entrepreneurial mindset, and change management, and crisis management. The sample size chosen for this research was 350 (including small, medium and large scale business enterprises operating in Pakistan). Data was collected over the time period ranging from May 05, 2021, to June 30, 2021, by utilizing the snow ball sampling technique.Our results show that business firms are dealing with multiple challenges and issues.Collected data confirmed that business operations of firms were greatly affected and the functioning of business is barely maintained. It was observed that business operations of 91% of different firms cumulatively are seriously interrupted. Business units believe that the top difficulty which is being faced by them is the negative effect of the precautionary measures taken to respond to the pandemic. Businesses are working with multiple strategies, to survive and enhance their stability to resistthe crisis.